Resistome Diversity and Dissemination of WHO Priority Antibiotic Resistant Pathogens in Lebanese Estuaries - Wadad Hobeika; Margaux Gaschet; Marie-Cécile Ploy; Elena Buelow; Dolla Karam Sarkis; Christophe Dagot (MDPI AG, 2022)
Anthropogenic pressure is known to be a key driver of antimicrobial resistance (AMR) dissemination in the environment. Especially in lower income countries, with poor infrastructure, the level of AMR dissemination is high. Therefore, we assessed the levels and diversity of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in Lebanese rivers at estuaries' sites (n = 72) of the Mediterranean Sea in spring 2017 and winter 2018. Methods: A combined approach using culture techniques and high throughput qPCR were applied to identify ARB and ARGs in rivers along the Lebanese coast. Results: Multidrug-resistant Gram-negative (Enterobacterales and Pseudomonas spp.) and Gram-positive bacterial pathogens were isolated. Levels of ARGs were highest in the winter campaign and areas with high anthropogenic activities and population growth with an influx of refugees. Conclusion: Qualitative analysis of ARB and the analysis of the Lebanese estuaries' resistome revealed critical levels of contamination with pathogenic bacteria and provided significant information about the spread of ARGs in anthropogenically impacted estuaries.